Toxicity of cryoprotectants on Prochilodus lineatus (Valenciennes, 1837) (curimba) embryos in an experimental incubator (Characiformes: Prochilodontidae) - Paula, Daniella A. J.; Machado, Mônica R. F.; Murgas, Luis D. S.; Rabelo, Denílson; Zangerônimo, Márcio G.; Reis Neto, Rafael Vilhena [UNESP]; Andrade, Estefânia S.; Andrade, Eliane A. (Sociedade Brasileira de Ictiologia, 2014)
This paper investigated the effect of cryoprotectant substances on Prochilodus lineatus embryos in an experimental incubator. The prospective study applied combinations of polyvinyl alcohol, hydroxyethyl cellulose, gelatin and fetal bovine serum with dimethyl sulfoxide and ethylene glycol in a new experimental incubator. The morphology of embryos, larval viability and the efficiency of experimental incubators in maintaining the quality of embryos were evaluated. This study demonstrates the efficient association between hydroxyethylcellulose and dimethyl sulfoxide as greater viability (p<0.05) was found for embryos (72.9 ± 23.9%). It should also be noted the permeation of cryoprotectants in embryos through the changes found in chorion diameter, embryo diameter and embryo volume comparing the treatments versus control group (water) (p<0.05), this results can help in future cryopreservation protocols. Although the temperature and oxygenation differed between the usual and experimental incubators (p<0.05), the results showed a high fertilization rate (79.6 ± 13.2%) for experimental incubators (p<0.05) which is sufficient for the maintenance of embryos in a cryoprotective environment and effectively allows experimentation for long periods with cryoprotectant substances. Cryopreservation of fish embryos has not been accomplished yet and new approaches are required for understanding the permeability of teleost embryos, especially in Brazilian native species.

Este trabalho avaliou o efeito de substâncias crioprotetoras sobre embriões de Prochilodus lineatus em uma incubadora experimental. O estudo aplicou combinações de álcool polivinílico, hidroxietilcelulose, gelatina e soro fetal bovino com dimetilosulfóxido e etilenoglicol em uma nova incubadora experimental. Foram avaliadas a morfologia dos embriões, a viabilidade larval e a eficiência das incubadoras experimentais na manutenção da qualidade dos embriões. Este estudo demonstra a associação eficiente entre hidroxietilcelulose e dimetilsulfóxido pela maior viabilidade (p<0,05) encontrada para os embriões (72,9 ± 23,9%). Deve-se notar também a permeação dos crioprotetores nos embriões através das alterações encontradas no diâmetro córion, diâmetro do embrião e no volume do embrião comparando os tratamentos ao grupo controle (água) (p<0,05), estes resultados podem ajudar em futuros protocolos de criopreservação. Embora a temperatura e a oxigenação diferiram entre as incubadoras comuns e as experimentais (p<0,05), os resultados mostraram elevada taxa de fertilização (79,6 ± 13,2%) para incubadoras experimentais (p<0,05), o que é suficiente para a manutenção de embriões em ambiente crioprotetor e permite efetivamente a experimentação por longos períodos com substâncias crioprotetoras. A criopreservação de embriões de peixes ainda não foi realizada e novas abordagens são necessárias para a compreensão da permeabilidade dos embriões de teleósteos, especialmente em espécies nativas brasileiras.